Distribution of Communication Disorders in Primary School Children - Jayashree C. Shanbal; Arunraj K; Madhu Sudharshan Reddy (Journal of All India Institute of Speech and Hearing, 1970)
Evidence regarding incidence and prevalence of a communication disorder is essential for early identi cation, rehabilitation and prevention of occur- rence of a disorder. The present study aimed to identify the distribution of communication disorders in primary school children. A total of 2010 primary school children had participated in the screening program for communication disorders. All the children were screened for speech and language disorders using various speech and language test tools. Theresults of the study revealed that around 11.5% of school children had some form of communication disorders. Among these, distribution of language disorders (7.4%) was in greater proportion when compared to speech disorders (3.8%) and multiple disorders (0.2%). Within thedisordered group, boys (66.7%) were more likely than girls (33.3%) to have had any communication disorder with a ratio of around 2:1. Theresults indicated the importance of identifying communication disorders in school children as young as possible. Often communication disorders go undetected at the early stage in school children and result in major impact in their social and academic life. The ndings of the study stress the need to plan for prevention strategies of communication disorders in terms of early identi cation and intervention in young children